Utilization of Different Probiotics on Growth and Survival Rate of Blacktail Zebra fish (Dascyllus melanurus) - Muchdar, Fatma; Juharni, Juharni; Andriani, Rovina (Sangia Research Media and Publishing, 2020)
Blacktail Zebra fish (Dascyllus melanurus) is more caught the sea by fishermen. There are several limitations which are lower growth and feet effisincy trought the natural habitat. Hence, an optimal feed combination is consideret to be provided during fish rearing to increase their growth. One of ideas was to use probiotic, which is bacteria that are able to decompose organic materials to change toxic compounds is valauable matter to the environment. For instance, ammonia and nitrite can be converted into free ammonium. The additional in an artificial feed is exfected to gain aquaculture activities. The study was conducted for 56 days from August to October 2019 in Wetlab Kastela FPK of Khairun University. Experiment and four treatments were applied using Filling Randomized Design (RAL). The result shows that different additional probiotic effected the growth and survival rate of Blacktail zebra fish. The highest was found in probio7 15 ml/kg feed, which gave 0,88g of total growth’; and the lowest was 0,27g which was found in the treatment A ((control)/ Water quality was checked weekly and in normal condition for the growth of the growth of blacktail zebra fish.